Survival and Intra-Nuclear Trafficking of Burkholderia pseudomallei: Strategies of Evasion from Immune Surveillance? - Vadivelu, Jamuna; Vellasamy, Kumutha Malar; Thimma, Jaikumar; Mariappan, Vanitha; Kang, Wen Tyng; Choh, Leang Chung; Shankar, Esaki Muthu; Wong, Kum Thong (Public Library of Science, 2017)
Background: During infection, successful bacterial clearance is achieved via the host immune system acting in conjunction with appropriate antibiotic therapy. However, it still remains a tip of the iceberg as to where persistent pathogens namely, Burkholderia pseudomallei (B. pseudomallei) reside/hide to escape from host immune sensors and antimicrobial pressure. Methods: We used transmission electron microscopy (TEM) to investigate post-mortem tissue sections of patients with clinical melioidosis to identify the localisation of a recently identified gut microbiome, B. pseudomallei within host cells. The intranuclear presence of B. pseudomallei was confirmed using transmission electron microscopy (TEM) of experimentally infected guinea pig spleen tissues and Live Z-stack, and ImageJ analysis of fluorescence microscopy analysis of in vitro infection of A549 human lung epithelial cells. Results: TEM investigations revealed intranuclear localization of B. pseudomallei in cells of infected human lung and guinea pig spleen tissues. We also found that B. pseudomallei induced actin polymerization following infection of A549 human lung epithelial cells. Infected A549 lung epithelial cells using 3D-Laser scanning confocal microscopy (LSCM) and immunofluorescence microscopy confirmed the intranuclear localization of B. pseudomallei. Conclusion: B. pseudomallei was found within the nuclear compartment of host cells. The nucleus may play a role as an occult or transient niche for persistence of intracellular pathogens, potentially leading to recurrrent episodes or recrudescence of infection.